Allergic Bronchopulmonary Mycosis Caused by Mucor Overlapping With Invasive Pulmonary Mucormycosis: A Case Report - Zhang, Ruhui; Jin, Ge; Zhan, Yasheng; Shen, Lisha; Yao, Yake; Gao, Qiqi; Yang, Qing; Zhou, Jianying; Zhou, Hua (Frontiers in Medicine, 2022)
Mucormycosis is a rare and invasive fungal infection with high mortality. Cases of invasive pulmonary mucormycosis that involve allergic reactions such as allergic bronchopulmonary mycosis are rarely reported. Herein, we describe a case of invasive pulmonary mucormycosis overlapping with allergic diseases in a patient who presented with eosinophilia and high total plasma immunoglobulin E (IgE). The patient was successfully treated with systemic corticosteroids (initial dose of prednisolone approximately 0.5 mg/kg per day, total duration less than 3 months) combined with posaconazole antifungal therapy. The treatment resulted in recovery of peripheral-blood eosinophil count and total plasma IgE, and significant reduction in lung lesions. A subsequent lobectomy was performed. The findings in this case indicate that systemic corticosteroid therapy may contribute to the treatment of pulmonary mucormycosis combined with allergic factors.